TYPES OF FILM TITLES IN UZBEK AND ENGLISH - Dilarom Safarova Abdukadirovna (Western European Studies, 2025)
This article explores the typology and formation of film titles in English and Uzbek languages. As reflections of cultural and aesthetic values, film titles vary significantly between linguistic and cultural systems. The study categorizes film titles into semantic, metaphorical, characterbased, and theme-based types. Furthermore, it provides a comparative analysis of naming trends in both languages, highlighting differences and similarities in linguistic structure, translation strategies, and cultural implications.
Keywords: Film titles; translation; culture